2010
DOI: 10.1073/pnas.0913638107
|View full text |Cite
|
Sign up to set email alerts
|

Origins of catalysis by computationally designed retroaldolase enzymes

Abstract: We have investigated recently reported computationally designed retroaldolase enzymes with the goal of understanding the extent and the origins of their catalytic power. Direct comparison of the designed enzymes to primary amine catalysts in solution revealed a rate acceleration of 10 5 -fold for the most active of the designed retroaldolases. Through pH-rate studies of the designed retroaldolases and evaluation of a Brønsted correlation for a series of amine catalysts, we found that lysine pK a values are shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
104
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(117 citation statements)
references
References 32 publications
11
104
0
2
Order By: Relevance
“…We next evaluated the ability of fluorescent probe 3 to distinguish functional RA from its nonfunctional soluble conformations, using a pH titration. Previous studies revealed that acidic conditions protonate the K210 lysine, thus reducing the concentration of functional RA (16). We observed that the k cat /K m values decreased on buffer acidification (Fig.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…We next evaluated the ability of fluorescent probe 3 to distinguish functional RA from its nonfunctional soluble conformations, using a pH titration. Previous studies revealed that acidic conditions protonate the K210 lysine, thus reducing the concentration of functional RA (16). We observed that the k cat /K m values decreased on buffer acidification (Fig.…”
Section: Resultssupporting
confidence: 55%
“…S1A), a common natural enzyme scaffold (15). A pK a -perturbed active site lysine residue [K210 (16), pK a of 6.6] (Fig. S1B) is used for catalysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the design process, several possible catalytic mechanisms were considered, and the necessary catalytic site was designed based on the proposed mechanistic requirements and ported into several protein scaffolds. The most active designs had k cat /k uncat values on the orders up to 10 5 [81]. In the case of RA95, further directed evolution of the original design increased the activity by another six orders of magnitude over 19 rounds of directed evolution, and with the mutations at 23 different amino acid positions (figure 5) [82,83].…”
Section: Retro-aldolasesmentioning
confidence: 99%
“…The molecular bases of these rate accelerations are often complex, using multiple steps, multiple catalytic mechanisms, and relying on numerous molecular interactions, in addition to those provided by the main catalytic groups. This complexity imposes a significant barrier to understanding how an enzyme's sequence impacts its function and, thus, on our ability to rationally design biocatalysts with new or enhanced functions (2)(3)(4).…”
mentioning
confidence: 99%